Kematangan Shop Drawing Sebagai Penentu Pekerjaan Ulang (Rework) Proyek Konstruksi - Ryan Immanuel; Bambang Endro Yuwono (Universitas Trisakti, 2020)
Construction project implementation mostly faced by rework. Rework couldn’t be avoided and is experienced in a construction world. Rework is defined as all physical work of construction committed more than once or re-work which is done by contractor in the implementation stage, and or an activity to eliminate works that have been done before as a part of construction project out of resource context, where there is no change order and making up the cost from the owner. Rework could give a bad impact to performance, work productivity,and cost directly or indirectly having it has a quite significant consequences. By considering the bad impact obtained has far-reaching consequences, hence efforts to reduce the occurrence of rework in construction project stage is highly needed. This research was conducted to prove the maturity of Shop Drawing as a Determinant of Rework Project Construction of Multilevel Buildings Research carried out by using questionnaires. Respondents at the main survey stage were shown to contractors who were carrying out multistorey construction projects in the DKI Jakarta and surrounding areas. Respondents who filled in theProject Manager questionnaire were 3 people, 7 Site Managers, 5 Supervisors, 6 Quality Controls, 4 Engineering staff. In this study, data analysis techniques are determined using the AHP (Analytical Hierarchy Process) method, aiming to determine the dominant factors (ranking) of the factors that cause rework inconstruction work to prove the maturity of Shop Drawing As Determine Project Rework Construction of multistorey buildings. The results of this study indicate that the maturity of shop drawings greatly determines the occurrence of rework in multistorey building projects.